(untitled) (Filološke pripombe, 2019)
This paper tries to open new ways of interpretation of Antun Šoljan’s Izdajice (1961). This text has often been presented in literary criticism as an apolitical text in the times of communist ideological imperative. My paper discusses the possibility of reading this text as a political text, starting from the position there are no apolitical texts. Strategy of permanent nomadism and resistance to institutional life of characters in the novel is interpreted through the theories of G. Deleuze and F.Guattari expressed in the text Nomadology and Hakim Bey’s theory of temporary autonom- ous zones. However, Izdajice is the ambivalent novel – indecision between nomadism as a resistent strategy and utopian escapism is obvious but the novel ends in pessimism and failure of characters’ life principles and attitudes.